PENGEMBANGAN STRATEGI PEMASARAN PADA SENTRA UMKM TELUR ASIN MELALUI DIGITAL MARKETING DI DESA SIMOKETAWANG, KEC. WONOAYU - Yulianti, Fransisca Eri; Pujianto, Wahyu Eko (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
This community service activity aims to help MSMEs "Telur Asin" in dealing with the impact of decreased income by providing assistance and training on the application of digital marketing. The method of implementing the training was carried out offline by involving the owner of MSME "Telur Asin" as a participant and involving direct discussion and questions and answers. In addition, the author also provides assistance in the form of making Gofood, Instagram, and optimizing digital media management. The results of this activity show the importance of MSME adaptation to technological advances to develop and compete in the current era of digitalization. In the title, the main focus is the transformation of "Telur Asin" MSMEs from offline businesses to online businesses through the use of social media and digital platforms such as Gofood and Instagram. This will help these MSMEs expand their target consumers and improve overall marketing.